Do We Care about Going Green? Measuring the Effect of Green Environmental Awareness, Green Product Value and Environmental Attitude on Green Culture. An Insight from Nigeria - Ogiemwonyi O.; Harun A.B.; Alam M.N.; Othman B.A. (Sciendo, 2023)
Least squares approximations; Surveys; Attitude; Environmental attitudes; Environmental awareness; Going green; Green culture; Green products; Nigeria; Path models; Product value; Young consumers; Developing countries; environmental economics; environmental values; green economy; policy implementation; policy making; sustainability; sustainable development; Nigeria